(untitled) (Ameghiniana, 2013)
GRAPTOLITES FROM THE Los SOMBREROS FORMATION, LOWER ORDOVICIAN IN THE EASTERN SLOPE OF THE TONTAL HILL, PRECORDILLERA FOLD BELT OF SAN JUAN. - An early Ordovician sequence made up by gray limestones and black shales, approximately 1.000 m thick, cropping out in the central Precordillera fold belt (San Juan Province) has be en studied. Structural analysis shows that the sequence is part of a tectonic wedge; low and high angle faults separate it at the base and the top from Upper Devonian-Ordovician rocks. Three graptolitic faunas were díscovered in the lower part of the sequence: the first one is composed by Dictyonema sp., the second one by Callograptus cf. salteri Hall and the third one by Tetragraptus quadribrachiatus (Hall), Tetragraptus amii Elles & Wood, Tetragraptus cf. fruticosus (Hall), Tetragraptus? sp., Phyllograptus anna Hall and Didymograptus sp. The fossil-bearing beds constitute 35 m of the whole sedimentary sequence; the two first graptolitic associatíons are assigned to the Tremadocian and the last one to the Arenigian.